(3JYQja abgGA GdeGdcjI (B( (3CUMGH GdEeGe eGdc (B)s - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s; (3QhGjI CHh GdMSf Ydj Hf eMeO Hf YHO Gddg Hf ehgH GdMPGais ((3eMeO Hf Ydi Hf YHO Gdedc GdbQTi YQa HGHf GdbGgQ s)
(3ChdgG (B:s
(3HOCg HJQLeI YHO Gddg Hf hgH s
(3BNQgG (B:s
(3GfJgi HJQLeI CHh eUYH GdRgQi s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B315s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B368 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B40 s
Keywords: (3GdJGQjNs